The Duration of the correction loss after removing cheneau brace in patients with adolescent idiopathic scoliosis - Zaborowska-Sapeta, Katarzyna (Acta Orthop Traumatol Turc, 2019)
OBJECTIVE: The aim of the study was to evaluate the loss of truncal rotation over 54 hours after removing Chêneau brace. METHODS: The studied groups consisted of 39 girls aged 10–18 years old, diagnosed with adolescent idiopathic scoliosis (AIS) and treated with Chêneau brace (CAST) and 20 AIS girls aged 10–18 years old, not treated with bracing. Posterior-anterior radiographs were obtained from the clinical assessment of all subjects and were subsequently used to determine Cobb angles. The measurements of the angle of trunk rotation (ATR) were taken with the Scoliometer® and back-contour device during Adams forward bending test by the two evaluators. The changes in ATRs during 54 hours of observation were performed after the brace had been taken off (0, 2, 24, 30, 48 and 54 hours after debracing). This was described using V(ATR) variable, defined as the change in the absolute Scoliometer® readings in the time intervals against the time interval Δt between the measurements. During back-contour assessment the differential factor (k(ra)) has been used for the digital analysis. The changes in k(ra) over 54 hours of observation were expressed as V(kra) factor, defined as the difference in the absolute value of the amplitude differential factor (k(ra)) in the time intervals against the time interval Δt between the measurements. RESULTS: The highest changes were observed in the thoracic as well as in lumbar spine in patients with Cobb angle ≥30°, axial rotation of the apical vertebrae within 5–15°, Risser sign 0–2. The biggest change in the trunk rotation after Chêneau brace had been taken off was noted within the first two hours of observation. CONCLUSION: The patients should be advised to take the brace off for a minimum of two hours before the scheduled x-ray, to allow full relaxation of the trunk in order to obtain reliable radiological images of the deformation. LEVEL OF EVIDENCE: Level III Therapeutic study.